Poor shoot and leaf growth in Huanglongbing-affected sweet orange is associated with increased investment in defenses - Neupane, Answiya; Shahzad, Faisal; Bernardini, Chiara; Levy, Amit; Vashisth, Tripti (Frontiers in Plant Science, 2023)
Citrus disease Huanglongbing (HLB) causes sparse (thinner) canopies due to reduced leaf and shoot biomass. Herein, we present results demonstrating the possible mechanisms behind compromised leaf growth of HLB-affected 'Valencia' sweet orange trees by comparing morphological, transcriptome, and phytohormone profile at different leaf development phases (1. buds at the start of experiment; 2. buds on day 5; 3. leaf emergence; 4. leaf expansion; 5. leaf maturation) to healthy trees. Over a period of three months (in greenhouse conditions), HLBaffected trees had ≈ 40% reduction in growth traits such as tree height, number of shoots per tree, shoot length, internodal length, and leaf size compared to healthy trees. In addition, buds from HLB-affected trees lagged by ≈ one week in sprouting as well as leaf growth. Throughout the leaf development, high accumulation of defense hormones, salicylic acid (SA) and abscisic acid (ABA), and low levels of growth promoting hormone (auxin) were found in HLB-affected trees compared to healthy trees. Concomitantly, HLB-affected trees had upregulated differentially expressed genes (DEGs) encoding SA, ABA, and ethylene related proteins in comparison to healthy trees. The total number of cells per leaf was lower in HLB-affected trees compared to healthy trees which suggests reduced cell division may coincide with low levels of growthpromoting hormones leading to small leaf size. Both bud dieback and leaf drop were higher in HLB-affected trees than healthy trees, with concomitant upregulated DEGs encoding senescence related proteins in HLB-affected trees that possibly resulted in accelerated aging and cell death.Taken together, it can be concluded that HLB-affected trees had higher tradeoff of resources on defense over growth, leading to sparse canopies and high tree mortality rate with HLB progression.